Virtual realities, real recoveries: exploring the efficacy of 3MDR therapy for treatment-resistant PTSD - Gausemel, Åsmund; Filkuková, Petra (Frontiers in Psychology, 2024)
Exposure-based therapies have shown promise in treating post-traumatic stress disorder (PTSD), but challenges exist in maintaining patient engagement and finding appropriate stimuli for graded exposure. Virtual reality (VR) technology has been used to enhance exposure therapy, but current software lacks customization and some patients remain treatment-resistant. A novel approach called multimodular motion-assisted memory desensitization and reconsolidation (3MDR) has the potential to solve some of the current limitations of VR-assisted exposure therapy. This study examines the efficacy of 3MDR treatment for individuals with treatment-resistant PTSD through a systematic review of relevant literature and clinical studies. Preliminary findings indicate promise for 3MDR in reducing PTSD symptoms, including emotional regulation and moral injury. However, further research with larger samples and controlled studies is needed to understand underlying mechanisms and validate these results. Moreover, this study highlights the importance of health-economic evaluations to assess costs and resource utilization associated with implementing 3MDR treatment in clinical services.